2011
DOI: 10.1007/s10495-011-0639-4
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFNs signaling and apoptosis resistance in glioblastoma cells

Abstract: Deletion of type I IFN genes and resistance to apoptosis induced by type I IFNs are common in glioblastoma. Here we have investigated the importance of the constitutive weak IFN-signaling in the apoptotic response to IFN-α in glioblastoma cells. U87MG cells hold a deletion of type I IFN genes, whereas in T98G cells the spontaneous IFN signaling is intact. In response to IFN-α U87MG cells produce much less TRAIL, while other IFN-inducible genes were efficiently up-regulated. Alterations in TRAIL promoter sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
(72 reference statements)
2
33
0
Order By: Relevance
“…Resistance to apoptosis is an intrinsic characteristic of glioblastoma (Eisele and Weller 2011;Sgorbissa et al 2001). Our data showed that treatment of glioblastoma cell lines with ZM results in a signiWcant degree of apoptosis in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 57%
“…Resistance to apoptosis is an intrinsic characteristic of glioblastoma (Eisele and Weller 2011;Sgorbissa et al 2001). Our data showed that treatment of glioblastoma cell lines with ZM results in a signiWcant degree of apoptosis in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 57%
“…Due to its ability to effectively stimulate host immune response in the setting of various solid tumors (13), IFN-α was the first cytokine to be approved for cancer treatment (4). IFN-α production by pDCs is regulated by the downstream signaling via the universal adapter protein MyD88 (myeloid differentiation primary response 88), upon stimulation of toll-like receptor (TLR)-7 and 9, which in turn acts via the constitutively expressed transcription factor IRF7 and the inflammatory transcription factor NF-κB, thereby initiating transcription of type I IFN (5).…”
Section: Introductionmentioning
confidence: 99%
“…29,38 Stealth RNA interference RNAi for USP18, TRAIL, and nontargeting shRNA were purchased from Invitrogen. Cells were transfected 24 h after plating by adding the medium OptiMem, containing Lipofectamine 2000 (Invitrogen) plus the stealth RNAi oligos.…”
Section: Methodsmentioning
confidence: 99%